Longitudinal evaluation of manual lymphatic drainage for the treatment of gynoid lipodystrophy - Bianca Schonvvetter; Juliana Laudicéia Marques Soares; Ediléia Bagatin (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: The gynoidlypodystrophy, known as cellulitis or cellulite, refers to a condition that gives the skin an undulating and uneven appearance, affecting 80-90% of women after puberty. OBJECTIVES: to investigate the efficacy and safety of manual lymphatic drainage for cellulite management. METHODS: this was an open, prospective, intervention study including 20 women aged from 20 to 40 years. Fourteen sessions of manual lymphatic drainage were performed once a week on lower limbs and buttocks. RESULTS: Fifteen women completed the study. A significant improvement on quality of life was observed (p=0.018). A significant reduction (p=0.023), estimated at 0.3±0.8 cm, in hip circumference was found, but no difference was found in thighs circumference (p>0.05). A significant reduction elastic recuperation of skin on buttocks, which means skin elasticity worsening, was observed. All measures obtained by ultrasound images showed no changes (p>0.05). CONCLUSION: manual lymphatic drainage was safe but not effective as an isolated approach for cellulite management. Further randomized, controlled or comparative studies about manual lymphatic drainage for cellulite control, as unique or combined therapeutic modality, are necessary.